AI-PERSONALIZED GREEN MARKETING: DRIVING ECO-CONSCIOUS CONSUMER BEHAVIOR IN REAL-TIME - Tio, Lina; Khan, Schazad; Yadewani, Dorris (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2026)
This study examines the integration of artificial intelligence in green marketing strategies, specifically focusing on personalized eco-engagement campaigns. Through a qualitative case study approach utilizing secondary data from The Body Shop Malaysia's sustainability initiatives, this research investigates how AI-driven personalization enhances eco-conscious consumer behavior. The findings reveal that AI-powered green marketing significantly improves consumer engagement rates, purchase intentions, and environmental awareness. This research contributes to the understanding of technology-enabled sustainable marketing practices in Southeast Asia and provides practical insights for businesses seeking to enhance their environmental impact through personalized digital strategies.